1998
DOI: 10.1521/jscp.1998.17.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Assault Perpetration by College Men: The Role of Alcohol, Misperception of Sexual Intent, and Sexual Beliefs and Experiences

Abstract: 1 99b) to explain one set of pathways through which alcohol and sexual assault are linked. It was hypothesized that the mutual effects of beliefs and experiences with regard to dating, sexuality, and alcohol increase the likelihood that a man would misperceive a female companion's sexual inten tions, and that this misperception would lead to sexual assault. Self-administered, anonymous surveys were conducted with a representative sample of 814 men at a large urban university. Twenty-six percent of these men re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
361
3
7

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 335 publications
(384 citation statements)
references
References 57 publications
13
361
3
7
Order By: Relevance
“…Additional verbal coercion items included a question about pressure induced through swearing, getting angry, or threatening to end the relationship as well as questions about verbally coerced oral and anal sex. Additional rape items assessed sexual intercourse when the woman was incapacitated and unable to give consent and a final question that specifically used the word "rape" [Abbey et al, 1998;Koss and Oros, 1982]. Each question was answered on a 6-point scale with options that ranged from never (0) to five or more times (6).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional verbal coercion items included a question about pressure induced through swearing, getting angry, or threatening to end the relationship as well as questions about verbally coerced oral and anal sex. Additional rape items assessed sexual intercourse when the woman was incapacitated and unable to give consent and a final question that specifically used the word "rape" [Abbey et al, 1998;Koss and Oros, 1982]. Each question was answered on a 6-point scale with options that ranged from never (0) to five or more times (6).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous researchers have replicated these basic findings. Depending on the university and exactly how questions were phrased, self-reported rates of sexual assault perpetration have been as high as 61% and rates of attempted or completed rape have been as high as 15% [Abbey et al, 1998[Abbey et al, , 2001Craig et al, 1989;Mills and Granoff, 1992;Muehlenhard and Linton, 1987;Rapaport and Burkhart, 1984;Wheeler et al, 2002].…”
Section: Self-reported Rates Of Sexual Assault Perpetration In Collegmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-five percent of these men reported that they had committed some form of sexual assault since the age of 14. In studies at individual universities and colleges, up to 15% of the men surveyed have indicated that they perpetrated rape and up to 57% indicated that they perpetrated some form of sexual assault (Abbey, McAuslan, & Ross, 1998;Craig, Kalichman, & Follingstad, 1989;Kanin, 1985;Mills & Granoff, 1992;Muehlenhard & Linton, 1987;Rapaport & Burkhart, 1984). More than 80% of these sexual assaults occurred with women these college perpetrators knew; about half occurred on dates.…”
Section: Samples Of College Menmentioning
confidence: 99%